PENGARUH MOTIVASI DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DAERAH - ABDUL GHONI, HUSEN Abdul (Jurnal Akuntansi AKUNESA, 2012)
This research aims to determine how much influence the motivation and knowledge of tax compliance to local taxpayers, particularly taxpayers billboard Surabaya area. Seeing the number of non-advertising firms in Surabaya in taxation obligations. This research uses qualitative methods to distribute the questionnaire to the respondent directly and indirectly. Questionnaire data obtained be calculated / tested using statistical software (SPSS17.0). Research has been conducted with statistical calculations show that motivation does not affect the taxpayer's compliance due to the perception that taxpayers are forced to pay taxes is not from personal desire. Knowledge significantly affects taxpayer compliance with local taxpayers. Key words: taxpayer compliance, qualitative methods, the taxpayer's perception